Open-Field Soilless Culture of Vegetables - George Hochmuth; Robert Hochmuth (EDIS)
This document is one of a series of Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 1996. Updated: January 2003.